2013
DOI: 10.1155/2013/492372
|View full text |Cite
|
Sign up to set email alerts
|

What Is Recent in Pancreatic Cancer Immunotherapy?

Abstract: Pancreatic cancer (PC) represents an unresolved therapeutic challenge, due to the poor prognosis and the reduced response to currently available treatments. Pancreatic cancer is the most lethal type of digestive cancers, with a median survival of 4–6 months. Only a small proportion of PC patients is curative by surgical resection, whilst standard chemotherapy for patients in advanced disease generates only modest effects with considerable toxic damages. Thus, new therapeutic approaches, specially specific trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 129 publications
(130 reference statements)
1
10
0
Order By: Relevance
“…These data support the idea that ENO1 could be a good candidate antigen for immunotherapeutic treatments in PDAC patients (49), in particular after surgical resection to prevent relapse of the disease through the marked anticancer activity of circulating ENO1-specific Tcc. Additional studies should be carried out to identify the different immunosuppressive mechanisms that are able to modify or switch off the anticancer specific immune response in order to make this immunotherapeutic approach feasible.…”
Section: Discussionsupporting
confidence: 80%
“…These data support the idea that ENO1 could be a good candidate antigen for immunotherapeutic treatments in PDAC patients (49), in particular after surgical resection to prevent relapse of the disease through the marked anticancer activity of circulating ENO1-specific Tcc. Additional studies should be carried out to identify the different immunosuppressive mechanisms that are able to modify or switch off the anticancer specific immune response in order to make this immunotherapeutic approach feasible.…”
Section: Discussionsupporting
confidence: 80%
“…Of note, Lepisto et al reported 33% four-year survival among 12 PDAC patients treated with MUC1 peptide-loaded dendritic cells (DC), 4,5 and Morse et al reported that 3 of 3 PDAC patients treated with CEA mRNA-transfected DC were alive with NED at 30 mo post-vaccination. 4,6 Additionally, several animal models have also established the utility of using total tumor antigens (mRNA or lysate) for DC immunotherapy, 7,8 a critical point given the significant contribution of desmoplasia to the total antigenic content of the pancreatic tumor. Old vaccination concepts for PDAC have also been given new life with the advent of immune checkpoint inhibitor drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic or autologous tumor cells can be used to develop vaccines. Advantages of whole cell vaccines include tumor cells can be grown in vitro , specifi c TAAs do not need to be identifi ed, polyclonal tumor specifi c T cell populations are generated, and cells can be altered to express surface proteins or secretable factors that induce strong immune responses [ 53 ]. One such example is granulocyte-macrophage colony stimulating factor (GM-CSF) secreting tumor cells.…”
Section: Whole Cell Vaccinesmentioning
confidence: 99%
“…It has been effective in both breast and gastric cancers, and is expressed in a signifi cant percent of pancreatic tumors [ 53 ]. Treatment with trastuzumab in mouse models has shown effi cacy.…”
Section: Antibody-based Therapiesmentioning
confidence: 99%